Technology, Application and Prospect of Integrated Sensing and Communication of Optical Networks - LIU Kewei; XIE Junjie; WU Bingbing; LI Fang (Guangtongxin yanjiu)
The integration of sensing and communication is beneficial of efficiently co-utilizing resources for optical networks. It empowers multi-dimensional sensing and ubiquitous optical communication, which is in line with the future development and evolution of optical network. The integrated optical network with sensing and communication capabilities can fully utilize existing fiber-optic network resources, enhance network quality and operational efficiency, and enable low-cost, high-efficiency, and high-reliability deployment and application of various novel fiber-optic sensing technologies. In this paper, we introduce the key technologies and technical challenges of integrated sensing and communication of optical networks. Then we elaborate and analyze several typical application scenarios. Finally, we discuss the prospective development of integrated sensing and communication of optical networks.